2006
DOI: 10.1086/504281
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric Emission Measurements on the Analogs of Individual Cosmic Dust Grains

Abstract: The photoelectric emission process is considered to be the dominant mechanism for charging of cosmic dust grains in many astrophysical environments. The grain charge and equilibrium potentials play an important role in the dynamical and physical processes that include heating of the neutral gas in the interstellar medium, coagulation processes in the dust clouds, and levitation and dynamical processes in the interplanetary medium and planetary surfaces and rings. An accurate evaluation of photoelectric emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Abbas et al 2006). Surprisingly, the large grain photoelectric yields measured by Abbas et al (2006) are much larger than theoretically expected.…”
Section: Dust Photoelectric Heatingmentioning
confidence: 73%
See 1 more Smart Citation
“…Abbas et al 2006). Surprisingly, the large grain photoelectric yields measured by Abbas et al (2006) are much larger than theoretically expected.…”
Section: Dust Photoelectric Heatingmentioning
confidence: 73%
“…Therefore, a full revision of the PE heating effect under disk conditions would be highly desirable, also because new laboratory results are available (e.g. Abbas et al 2006). Surprisingly, the large grain photoelectric yields measured by Abbas et al (2006) are much larger than theoretically expected.…”
Section: Dust Photoelectric Heatingmentioning
confidence: 99%
“…The reason is that a photo-electron can more easily be trapped within the matrix of a large grain, thus lowering the photoelectric yield. Experimental data on realistic astrophysical dust grains is sparse and only recently (Abbas et al 2006) carried out experiments with sub-micron to micron sized individual dust grains. They measure yields that are larger than those of bulk flat surfaces and they find an increasing yield with increasing grain size.…”
Section: Photo-electric Heatingmentioning
confidence: 99%
“…The photoelectron emission yield of carbonaceous grains with a radius of about 400 nm is about 10 −5 at the wavelength of 160 nm and 10 −4 at 140 nm and the yield increases with the size of particles. Thus, based on the calculations of Weingartner et al (2006) and the low photoelectron emission yield of Abbas et al (2006), we believe it is reasonable that dust particles in the outflow cavities of the RR are at least partially ionized and contain both neutral PAH molecules and some charged PAH ions. The neutral PAH molecules in the dust particles could emit red PL under irradiation by UV photons, as is observed in the outflow cavities of the RR.…”
Section: Ionization State Of the Ere Carriermentioning
confidence: 91%
“…From their Figure 4 we can see that that the ionization of small dust grains begins with photon energies greater than ∼6 eV, slightly higher than that required to ionize the filmy-QCC material. Abbas et al (2006) measured the yield of photoelectric emission of astronomical dust candidates experimentally. They showed that the yield also depends on the wavelength of the photon and the particle size of grains.…”
Section: Ionization State Of the Ere Carriermentioning
confidence: 99%